2021
DOI: 10.1016/j.jshs.2020.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of the 30–15 Intermittent Fitness Test: A systematic review

Abstract: Highlights The 30–15 Intermittent Fitness Test has excellent test-retest reliability for maximal velocity. Excellent test-retest reliability was also noted for peak heart rate. This test may be used as a reliable measure of fitness in research and sports practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
2
22
1
3
Order By: Relevance
“…When calculated from the same data, one study demonstrated that six different types of ICC ranged from 0.51 to 0.87 [68]. This issue is not limited to the studies included herein as recent reviews that focused on the test-retest reliability of the Yo-Yo test and the 30-15 Intermittent Fitness Test (30-15 IFT) also highlighted this as a limitation [69,70]. Even though not all studies reported the specific type of ICC types they used, 92% of all ICCs were still ≥ 0.90, suggesting that this limitation might not have had a profound impact on the findings of this review.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 91%
“…When calculated from the same data, one study demonstrated that six different types of ICC ranged from 0.51 to 0.87 [68]. This issue is not limited to the studies included herein as recent reviews that focused on the test-retest reliability of the Yo-Yo test and the 30-15 Intermittent Fitness Test (30-15 IFT) also highlighted this as a limitation [69,70]. Even though not all studies reported the specific type of ICC types they used, 92% of all ICCs were still ≥ 0.90, suggesting that this limitation might not have had a profound impact on the findings of this review.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 91%
“…Players were told to complete as many stages as possible, and the test was ended when the players could not maintain the required running speed or could not reach the 3-m zone before the beep three consecutive times. The final velocity registered in the last stage determined the player’s V IFT score ( Buchheit et al, 2009 ; Grgic et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…There are a number of monitoring tools and parameters to assist in this individualization process such as aerobic power (Milanez et al, 2011), the end speed of the 30-15 intermittent fitness tests (Malone et al, 2018a;Grgic et al, 2020), the anaerobic speed reserve (Buchheit and Mendez-Villanueva, 2014), muscle power (Loturco et al, 2019), heart rate variability (Rave et al, 2018(Rave et al, , 2019, countermovement jump performance (Claudino et al, 2012), the force-velocity profile (Mendiguchia et al, 2016), HR measures during specific drills (Lacome et al, 2018), wellbeing questionnaires (Malone et al, 2018b), or individualized training loads modeling (Bartlett et al, 2017) among others. Specific monitoring tools should be selected and adapted to each sport and setting while developing the athlete monitoring cycle (Gabbett et al, 2017).…”
Section: The Individualization Approach In Team Sportsmentioning
confidence: 99%